The Influence of Islamic Financial Literacy on Financial Behavior Among Students of Bandung State Polytechnic (Case Study of Islamic Finance Students at Bandung State Polytechnic) - Nayla Sandra Aulia*; Giri Lazuardi Hendrawan (Universitas Syiah Kuala, 2023)
This research aims to determine the influence of the level of Islamic financial literacy on financial behavior among students of Islamic finance at Bandung State Polytechnic. The variables in this study are the level of Islamic financial literacy (X) and financial behavior (Y). The method employed in this research is a quantitative descriptive approach. Data collection was conducted through a questionnaire distributed via Google Form. The respondents in this study are all students of the Islamic Finance Program at Bandung State Polytechnic, totaling 256 individuals. The sample size was calculated using the Slovin formula with a 0.05 level of error, resulting in a sample of 156 individuals. Subsequently, the relationship between the two variables was analyzed using simple linear regression, computed using SPSS software version 25. The results of this research indicate that the Islamic Financial Literacy variable has a positive and significant influence on financial behavior among students of the Islamic Finance Program at Bandung State Polytechnic.